Managerial ability of the management influence on employee performance of the republic of Indonesia employee cooperative (KPRI) Pengayoman City Makassar - Romansyah Sahabuddin; Deddy Ibrahim Rauf; Raissa Muhayminah Arimansah Putri; Lutfillah Nursadrina S; Lutfin Mufida; A. Dara Nurfadilah; Ahmad Rifani (International Journal of Applied Finance and Business Studies, 2023)
The mission of this research was to determine the ability of management in influencing employee performance at the Republic of Indonesia Employee Cooperative (KPRI) Pengayoman Makassar City. This research variable has an independent variable, namely the management ability of the board (X1) and the dependent variable, namely employee performance (Y). This study method uses descriptive analysis with a quantitative approach and descriptive research includes data collection to test hypotheses and use statistical tests. Based on the results of the study, a simple linear regression equation = 9.949 + 0.889 (X) was obtained. The results of the simultaneous test state that the simultaneous count is = 83.278 and significant = 0.000 <0.05, which means that the hypothesis: "There is a significant influence of management ability management on employee performance at the Indonesian Republic Employee Cooperative (KPRI) Pengayoman Makassar City" is accepted. Meanwhile, from hypothesis testing in the t test (Pasrial test), the t count of the management ability variable is 9.126 and if the probability is less than 0.05, the hypothesis tested is partially accepted. The coefficient of determination (adjusted R2) is 0.410. This means that 41% of employee performance at the Indonesian Republic Employees Cooperative (KPRI) Pengayoman Makassar City is influenced by management capabilities and the remaining 59% is influenced by other variables outside those examined in the study.